2018
DOI: 10.1093/cercor/bhy134
|View full text |Cite
|
Sign up to set email alerts
|

To Move or Not to Move? Functional Role of Ventral Premotor Cortex in Motor Monitoring During Limb Immobilization

Abstract: Anatomo-clinical evidence from motor-awareness disorders after brain-damages suggests that the premotor cortex (PMC) is involved in motor-monitoring of voluntary actions. Indeed, PMC lesions prevent patients from detecting the mismatch between intended, but not executed, movements with the paralyzed limb. This functional magnetic resonance imaging study compared, in healthy subjects, free movements against blocked movements, precluded by a cast. Cast-related corticospinal excitability changes were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…4a). This structural temporofronto-parietal connectivity pattern is highly compatible with the role of ventral PMC as a comparator system 2,7-9 , proposed by lesion studies in AHP patients 2,7-9 and by neuroimaging studies in healthy subjects 32,[44][45][46][47] . For instance, ventral PMC has been recently described as the neural correlate of motor-monitoring during mechanical limb immobilization.…”
Section: Cs Precssupporting
confidence: 63%
See 3 more Smart Citations
“…4a). This structural temporofronto-parietal connectivity pattern is highly compatible with the role of ventral PMC as a comparator system 2,7-9 , proposed by lesion studies in AHP patients 2,7-9 and by neuroimaging studies in healthy subjects 32,[44][45][46][47] . For instance, ventral PMC has been recently described as the neural correlate of motor-monitoring during mechanical limb immobilization.…”
Section: Cs Precssupporting
confidence: 63%
“…(1) A positive effect in altering motor execution was expected based on previous literature employing DES during the same HMt 12,14,15 . (2) A positive effect in altering the motor awareness was expected based on anatomical and functional evidence in AHP patients 2,7-9,48,49 and in healthy subjects 44,45 . It is important to note that lesion studies in AHP patients also highlight the role of other brain areas putatively relevant for motor unawareness, such as the temporo-parietal junction 48 and the insula 48,50 .…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, in that study, it has been also found an enhanced/more rigid sense of body ownership for the (healthy) not immobilized hand (where the strength of the RHI is decreased). According to previous TMS studies on both immobilization procedure in healthy subjects (Avanzino, Bassolino, Pozzo, & Bove, ) and constraint‐induced movement therapy (CIMT) in brain‐damaged patients (Wittenberg & Schaechter, ), which showed increased activity of the hemisphere ipsilateral to the immobilized limb (for a different result see Garbarini et al., ), the decreased RHI susceptibly for the intact hand of hemiplegic patients can be due to hyper‐use of the intact side. If this is the case, future experiments assessing the complementary effect of high‐frequency rTMS, known to increase the M1 corticospinal excitability (Arai et al., ; Maeda, Keenan, Tormos, Topka, & Pascual‐Leone, ), should document a reduced RHI susceptibility.…”
Section: Discussionmentioning
confidence: 98%